Retrospective Study Analyzing Risk Factors of Foot and Ankle Amputation in Patients with Diabetes Diagnosed with Osteomyelitis. Issue 1 (January 2022) - Efejuku, Tsola; Chokshi, Shivan N.; Jupiter, Daniel; Chen, Jie; Panchbhavi, Vinod K.
Category: Ankle; Diabetes; Midfoot/Forefoot Introduction/Purpose: Osteomyelitis is an invasive infection of the bone that commonly afflicts patients with diabetes mellitus. This bacterial infection can lead to the need for amputation of portions of the foot or ankle. While the association between Osteomyelitis and amputation has been studied, little is known about additional underlying health conditions that can predispose diabetic patients to an increased risk of amputation. Understanding these relationships will be useful in early screening to prevent severe effects associated with the loss of the foot or ankle. Thus, a retrospective analysis was performed using EMR data to evaluate the effect of prior Peripheral Vascular Disease (PVD) or Neuropathy on amputations in Type 2 DM patients with Osteomyelitis. Methods: Patients with Type 2 Diabetes Mellitus and Osteomyelitis who had a foot or ankle amputation within 12 weeks of diagnosis, compared to those who also had PVD or neuropathy were identified. This was done in the EMR database using ICD 10 codes for Osteomyelitis (M86), Type 2 Diabetes Mellitus diagnosis (E11), Foot or Ankle amputations (1005524, 1005529, 28810, 1005525, 28805, 1800300006, 371186005, 180040009, 726651003, 723726002, 723731000, 180038004, 78785006, 28800, 180157006, 723312009, 773821000, 773819005, 397218006), Peripheral Vascular Diseases (I73), and Neuropathy (G62). We then stratified these patients by age (18-29, 30-39, 40-49, 50-59, 60-69, 70-79, 80-89), gender (male, female), and year by decade (2001, 2010, and 2020). Results: Our search identified 125, 741 patients with T2DM and Osteomyelitis, of whom 10, 850 had a foot or ankle amputation within 3 months of diagnosis. 28, 242 patients with T2DM, Osteomyelitis, and prior PVD were identified. These patients were found to be 2.6 times more likely to receive a foot or ankle amputation. 12, 860 patients with prior Neuropathy were identified.. These patients were found to have 1.36 times more likely to receive a foot or ankle amputation. When stratified by gender, Women were found to be at greater risk of Amputation than Men, for both prior PVD and Neuropathy (2.9 vs 2.47 times greater risk, respectively). Age stratification revealed patients aged 50-59 have the highest risk for a foot or ankle amputation (10% higher risk). This was more than triple the risk seen in patients aged 18-29. The above differences were found to be statistically significant at a p-value of <.0001. Conclusion: This analysis provides insight into the pre-disposing risk factors of Foot and Ankle amputations in patients who have Type 2 Diabetes Mellitus and Osteomyelitis. Of the two risk factors analyzed, Peripheral Vascular Disease was associated with the highest risk of amputation. Overall, females and patients aged 50-59 are at the highest risk of amputation with underlying PVD. As comorbidities become more frequent and the number of foot or ankle amputations continues to rise since 2001, more research on associated risk factors will be necessary to more effectively screen these patients.